IMPLEMENTASI STRATEGI PEMBELAJARAN RELATING, EXPERIENCING, APPLYING, COOPERATING, TRANSFERING DI SEKOLAH MENENGAH PERTAMA - Endang Kurniawati; Edy Yusmin; Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aimed to describe the implementation of the REACT strategy (relating, experiencing, applying, cooperating, transfering) on the curved surfaces at grade IX B SMP Negeri 6 Pontianak. The research method was experiment method with a one case study design. The techniques of data collection used in this research were observation, test, and indirect communication with the instruments used were the learning implementation observation sheets, the student learning activity observation sheets, the learning outcomes tests, and the student response questionnaires. Based on the results of research and the data analysis, it was found that the implementation of learning with the REACT strategy was classified as good with an average score of 3.14, student learning activities with the REACT strategy were classified as active with an average percentage of 77.35%, classical student learning completeness had not been fulfilled by the percentage of students who achieved the completeness criteria was only 30%, and the student's response to learning the REACT strategy was positive with a score of 1.6861. Keywords: Curved surfaces, Implementation, REACT strategy,